2017
DOI: 10.1002/aur.1912
|View full text |Cite
|
Sign up to set email alerts
|

Is food refusal in autistic children related to TAS2R38 genotype?

Abstract: A variation of the gene TAS2R38, associated with bitter taste sensitivity, can cause a different perception of some foods. In particular, some children are hypersensitive to bitterness and show a more restricted repertoire of accepted foods. We evaluate bitter sensitivity in ASD children with or without food selectivity, through a simple bitter taste test with edible strips. The results show that food refusal in ASD children can be mediated by bitter taste sensitivity thus suggesting that the bitter sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
1
15
0
12
Order By: Relevance
“…Sendo assim, um dos principais desafios é avaliar os fatores sensoriais e padrões alimentares restritivos e repetitivos em crianças com autismo, para determinar quais as abordagens devem ser adotadas da maneira mais precoce possível (YAMANE; FUJII; HIJIKATA, 2020). A intervenção precoce auxilia em tornar alimentos mais palatáveis, garantindo assim uma adequada oferta de fatores nutricionais, principalmente no início da infância (RICCIO et al, 2018).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sendo assim, um dos principais desafios é avaliar os fatores sensoriais e padrões alimentares restritivos e repetitivos em crianças com autismo, para determinar quais as abordagens devem ser adotadas da maneira mais precoce possível (YAMANE; FUJII; HIJIKATA, 2020). A intervenção precoce auxilia em tornar alimentos mais palatáveis, garantindo assim uma adequada oferta de fatores nutricionais, principalmente no início da infância (RICCIO et al, 2018).…”
Section: Discussionunclassified
“…No TEA, a severidade da recusa e a persistência em certos alimentos se devem principalmente à ativação de padrões específicos da sensibilidade gustativa e características neuropsicológicas típicas do transtorno, como a rigidez comportamental (RICCIO et al, 2018). A recusa alimentar apresentada por diversos indivíduos na amostra coloca-os em situação de atenção nutricional, considerando as possíveis carências nutricionais que essas pessoas podem apresentar, afetando diretamente seu estado nutricional.…”
Section: Discussionunclassified
“…Likewise, Bandini et al found that FFQ data revealed children with ASD refuse more vegetables than TD children [42]. In agreement with this, a study found that food refusal in children with ASD may in some cases be due to a bitter taste sensitivity associated with the TAS2R38 genotype [47]. Although little research has investigated the implications of polymorphisms in taste receptors and feeding behaviors in ASD, previous research has demonstrated that TD children exhibit two sensitive alleles for bitter taste had a lower threshold concentration to detected sucrose and a greater sugar consumption compared to children with less sensitive alleles [48].…”
Section: Feeding Behaviormentioning
confidence: 78%
“…Aberrant EBs are complex issues of ASD. Riccio's research proved that aberrant EBs, in particular food selectivity was mediated by taste sensitivity which related to TAS2R38 genotype ( 21 ). Messina's study presented that the rule of sympathetic activity was very important for ASD, neurotransmitters alterations could explain food selectivity ( 22 ), and further study could broaden horizons to multi-modal approach.…”
Section: Discussionmentioning
confidence: 99%